2021
DOI: 10.3390/biomedicines9101490
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial versus Direct Cortical Stimulation for Motor-Evoked Potentials during Resection of Supratentorial Tumors under General Anesthesia (The TRANSEKT-Trial): Study Protocol for a Randomized Controlled Trial

Abstract: Background: Monitoring of motor function during surgery for supratentorial tumors under general anesthesia applies either transcranial electrical stimulation (TES) or direct cortical stimulation (DCS) to elicit motor-evoked potentials. To date, there is no guideline that favor one method over the other. Therefore, we designed this randomized study to compare between both methods regarding the prediction of postoperative motor deficits and extent of tumor resection. Methods: This is a multicenter (six centers i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Intraoperative MEPs are the gold standard for supratentorial glioma surgery in eloquent areas ( Al-Adli et al, 2023 ). The two techniques by which the MEPs can be evoked are transcranial stimulation (TES), that utilize a high-voltage electrical stimulus through the scalp/skull to activate the motor cortex and descending pathways, and DCS, by stimulating through a strip electrode that is placed over the primary motor cortex ( Abboud et al, 2021 ). The predictive value for postoperative motor deficit is high, but it has been suggested that DCS has a higher reliability, independently of the location of the tumors and the position of the patient ( Viganò et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative MEPs are the gold standard for supratentorial glioma surgery in eloquent areas ( Al-Adli et al, 2023 ). The two techniques by which the MEPs can be evoked are transcranial stimulation (TES), that utilize a high-voltage electrical stimulus through the scalp/skull to activate the motor cortex and descending pathways, and DCS, by stimulating through a strip electrode that is placed over the primary motor cortex ( Abboud et al, 2021 ). The predictive value for postoperative motor deficit is high, but it has been suggested that DCS has a higher reliability, independently of the location of the tumors and the position of the patient ( Viganò et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that transcranial stimulation and recordings are less speci c than direct cortical in brain surgery. This is because the distance from the electrode to the functional brain area at risk is larger when recording or stimulating through the skull (11). We also assumed that multimodality IONM should be preferred to unimodal (12).…”
Section: Methodsmentioning
confidence: 99%
“…Transcranial MEPs (tcMEPs) utilize a high-voltage electrical stimulus through the scalp/skull to activate the motor cortex and descending pathways to generate an MEP, which can be measured by electrodes on the limbs. Alternatively, MEPs can be obtained by direct cortical stimulation (dcMEPs) after opening the dura by stimulating through a strip electrode that is placed over the primary motor cortex [ 44 ]. Following ‘train of 5’ anodal stimulation, a drop in signal amplitude by >50%, with the same stimulus intensity serving as the baseline established at the beginning of the case, or a 20% increase in the stimulus threshold needed to achieve a response compared to the ipsilateral muscle groups, are generally considered to be warning signals for postoperative weakness, and are monitored with the goal of avoiding false negative (i.e., normal MEP signals in patients who ultimately suffer from postoperative weakness) and overly sensitive false positive stimulation results (i.e., drops in MEP amplitude in patients without postoperative motor deficits) [ 45 , 46 ].…”
Section: Nuances Of Intraoperative Motor Mapping Techniques and Measu...mentioning
confidence: 99%